Fusarium and mycotoxin spectra in Swiss barley are affected by various cropping techniques. Issue 10 (2nd October 2016) - Schöneberg, Torsten; Martin, Charlotte; Wettstein, Felix E.; Bucheli, Thomas D.; Mascher, Fabio; Bertossa, Mario; Musa, Tomke; Keller, Beat; Vogelgsang, Susanne
ABSTRACT: Fusarium head blight is one of the most important cereal diseases worldwide. Cereals differ in terms of the main occurring Fusarium species and the infection is influenced by various factors, such as weather and cropping measures. Little is known about Fusarium species in barley in Switzerland, hence harvest samples from growers were collected in 2013 and 2014, along with information on respective cropping factors. The incidence of different Fusarium species was obtained by using a seed health test and mycotoxins were quantified by LC-MS/MS. With these techniques, the most dominant species, F. graminearum, and the most prominent mycotoxin, deoxynivalenol (DON), were identified. Between the three main Swiss cropping systems, Organic, Extenso and Proof of ecological performance, we observed differences with the lowest incidence and toxin accumulation in organically cultivated barley. Hence, we hypothesise that this finding was based on an array of growing techniques within a given cropping system. We observed that barley samples from fields with maize as previous crop had a substantially higher F. graminearum incidence and elevated DON accumulation compared with other previous crops. Furthermore, the use of reduced tillage led to a higher disease incidence and toxin content compared with samples from ploughed fields. Further factors increasing Fusarium infection were high nitrogen fertilisation as well as the application of fungicides and growth regulators. Results from the current study can be used to develop optimised cropping systems that reduce the risks of mycotoxin contamination.